2021
DOI: 10.3390/pathogens10091157
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Fluorometric Isothermal LAMP Assay for Detection of Chlamydia pecorum in Rapidly Processed Ovine Abortion Samples: A Veterinary Practitioner’s Perspective

Abstract: Traditional methods of detecting Chlamydia pecorum in tissue samples such as polymerase chain reaction or cell culture are laborious and costly. We evaluated the use of a previously developed C. pecorum LAMP assay using minimally processed ovine samples. Cotyledon (n = 16), foetal liver (n = 22), foetal lung (n = 2), and vaginal (n = 6) swabs, in addition to cotyledon (n = 6) and foetal liver (n = 8) tissue samples, were rapidly processed and used for LAMP testing without DNA extraction. Overall, LAMP test res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…In this study, we also demonstrated the successful use of rapid isothermal assay of rapidly processed swabs to detect PhaHV-1 infections, supporting the proof of concept that rapid isothermal diagnostics can be applied at the koala and/or other veterinary clinical setting [33,35,36]. Similar to Chlamydia isothermal assays [26,27], the PhaHV-1 isothermal assay performed in the Genie III fluorometer provides straightforward interpretation of results, with positive results being distinctly characterised by amplification time and specific melt curves.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In this study, we also demonstrated the successful use of rapid isothermal assay of rapidly processed swabs to detect PhaHV-1 infections, supporting the proof of concept that rapid isothermal diagnostics can be applied at the koala and/or other veterinary clinical setting [33,35,36]. Similar to Chlamydia isothermal assays [26,27], the PhaHV-1 isothermal assay performed in the Genie III fluorometer provides straightforward interpretation of results, with positive results being distinctly characterised by amplification time and specific melt curves.…”
Section: Discussionsupporting
confidence: 66%
“…To evaluate the use of rapidly processed swabs in the PhaHV-1 assay, we used a total of 36 mucosal swabs (Minitip Rayon dry Aluminium shaft (Copan, Brescia, Italy) obtained from 16 ocular, 15 urogenital, one nasal and four rectal sites from 17 koalas. Swabs were processed in 300 μL of water by vortexing for 45 sec and heat lysis at 90°C for 10 min, as previously described [ 26 , 33 ]. All swabs were collected by qualified veterinarians as a part of routine health and diagnostic investigations.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the use of a C. pecorum LAMP assay for sheep infections, Clune and colleagues found that a C. pecorum LAMP assay agreed with the reference qPCR results in 80.4% and 85.71% when testing ovine swab and tissue samples, respectively. The authors concluded that, following further optimisation, LAMP testing is promising as a simple, low-cost, and accurate POC C. pecorum detection method [ 12 ].…”
Section: Chlamydial Infections In Livestock: a Global Concern For Eco...mentioning
confidence: 99%